Cashew Nut Shell Liquid (CNSL) as a Source of Drugs for Alzheimer’s Disease - Elisa Uliassi; Andressa Souza de Oliveira; Luciana de Camargo Nascente; Luiz Antonio Soares Romeiro; Maria Laura Bolognesi (Molecules, 2021)
Alzheimer’s disease (AD) is a complex neurodegenerative disorder with a multifaceted pathogenesis. This fact has long halted the development of effective anti-AD drugs. Recently, a therapeutic strategy based on the exploitation of Brazilian biodiversity was set with the aim of discovering new disease-modifying and safe drugs for AD. In this review, we will illustrate our efforts in developing new molecules derived from Brazilian cashew nut shell liquid (CNSL), a natural oil and a byproduct of cashew nut food processing, with a high content of phenolic lipids. The rational modification of their structures has emerged as a successful medicinal chemistry approach to the development of novel anti-AD lead candidates. The biological profile of the newly developed CNSL derivatives towards validated AD targets will be discussed together with the role of these molecular targets in the context of AD pathogenesis.